The Emergence of Religious Moderation in Indonesia’s Multicultural Society - Salma Khoerunisa; Shahibah Yuliani (Jurnal Indonesia Studi Moderasi Beragama, 2025)
Background: Conceptual ambiguity around religious moderation and tolerance persists in Indonesia’s plural society, complicating both discourse and practice. Objective: To clarify the meanings and limits of religious moderation and tolerance through a focused review. Method: This library research, conducted in 2023, used documentation to gather sources and applied Miles and Huberman’s stages of data reduction, data display, and conclusion drawing. Results: The literature converges on moderation as a middle path that aligns religious commitment with local wisdom and civic coexistence. Tolerance is framed as respectful acceptance of difference within legal and ethical boundaries. Moderation delineates boundaries that avoid both relativism and extremism while encouraging reflective dialogue, empathy, and shared responsibility. Conclusion: Religious moderation functions as a culturally grounded strategy for sustaining social harmony in Indonesia, enabling principled faith practice alongside mutual respect in daily life. Contribution: This review synthesizes dispersed scholarship into a coherent conceptual map, proposes working definitions and limits suited to the Indonesian context, and offers a baseline for curriculum design, policy guidance, community programming, and subsequent empirical testing, including indicators to inform evaluation and future comparative studies across regions and media.